1993
DOI: 10.1002/anie.199306501
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination Chemistry of Multidentate Isocyanide Ligands

Abstract: In spite of the excellent ligation properties of isocyanides, until a few years ago there was only a small number of known multidentate ligands of this type. One of the reasons for this lack of interest, when compared to monodentate isocyanides, was the linear arrangement of the M-C=N-R group, which usually inhibits the formation of mononuclear chelate complexes and leads to the formation of multinuclear or polymeric metal complexes. In these, the multidentate ligand acts in a monodentate Fdshion towards each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 140 publications
2
63
0
1
Order By: Relevance
“…Compared to a-diimine ligands such as 2,2'-bipyridine, there has been surprisingly little prior work on chelating isocyanide ligands, [18] particularly with regard to luminescent metal complexes. [19] We prepared the new 2,2''-diisocyano-3,5,3'',5''-tetramethyl-1,1':3',1''-terphenyl (CNAr 3 NC) ligand and reacted it with Mo(THF) 2 Cl 4 in the presence of Na/Hg to obtain the Mo(CNAr 3 NC) 3 complex shown in Figure 1 (pages S2-S5 in the Supporting Information).…”
Section: Ru(bpy)mentioning
confidence: 99%
“…Compared to a-diimine ligands such as 2,2'-bipyridine, there has been surprisingly little prior work on chelating isocyanide ligands, [18] particularly with regard to luminescent metal complexes. [19] We prepared the new 2,2''-diisocyano-3,5,3'',5''-tetramethyl-1,1':3',1''-terphenyl (CNAr 3 NC) ligand and reacted it with Mo(THF) 2 Cl 4 in the presence of Na/Hg to obtain the Mo(CNAr 3 NC) 3 complex shown in Figure 1 (pages S2-S5 in the Supporting Information).…”
Section: Ru(bpy)mentioning
confidence: 99%
“…complexes with monodentate arylisocyanide ligands are very strong photoreductants, capable, for example, of reducing anthracene to its radical anion form. Many different kinds of metal complexes with isocyanide ligands have been explored over the past few decades [11][12][13][14][15], but metals with the d 6 or d 10 electron configurations are unique in their ability to show luminescence from a 3 MLCT excited state.Whilst structurally more flexible, multidentate isocyanide chelate ligands had been known for some time [16], we found that chelating diisocyanide ligands based on a m-terphenyl backbone permit the synthesis of homoleptic tris(diisocyanide) complexes of Cr 0 and Mo 0 that luminesce from 3 MLCT excited states (Figure 1) [17]. The molecular and the electronic structures of these compounds are reminiscent of Fe II and Ru II polypyridine complexes, which have been investigated extensively in the past.…”
mentioning
confidence: 99%
“…Whilst structurally more flexible, multidentate isocyanide chelate ligands had been known for some time [16], we found that chelating diisocyanide ligands based on a m-terphenyl backbone permit the synthesis of homoleptic tris(diisocyanide) complexes of Cr 0 and Mo 0 that luminesce from 3 MLCT excited states (Figure 1) [17]. The molecular and the electronic structures of these compounds are reminiscent of Fe II and Ru II polypyridine complexes, which have been investigated extensively in the past.…”
mentioning
confidence: 99%
“…The pioneering contributions from the groups of Minghetti and Bonati,14 as well as Hahn,15 on the synthesis of metal carbenes starting from metal‐coordinated isonitriles, inspired us to develop an alternative strategy for the synthesis of Pd–PEPPSI complexes. Preparing NHC ligands through an isonitrile strategy not only offers a route to unsymmetrically substituted NHC ligands, but also avoids a stepwise pre‐synthesis of the corresponding imidazolium salts.…”
Section: Introductionmentioning
confidence: 99%